Legal Certainty in the Application of the Imposition of Moratoir Interest as a Legal Effect in Default - Nadia Rohadatul Aisyi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The payment of interest as compensation must be stated in the agreement between the creditor and the debtor, but there are several cases where moratoir interest is not specified in the agreement. For example, there is a case of default in the sale and purchase between Sri Mulyawati against PT Harmas Jalasveva and Real Estate Indonesia (REI) and a case of default in debt and credit between Tusrilawati against Marzuki. The purpose of this study is to determine the application of the imposition of moratoir interest and legal certainty about the application of the imposition of moratoir interest. The method used is normative juridical with a statutory approach and conceptual approach. As a result, the imposition of moratoir interest can be applied as a legal consequence in default even without an agreement related to late fees by the parties to the agreement. The imposition of moratoir interest can also be applied as a late penalty for payments that do not determine the amount of the penalty. However, in the absence of an agreement, the application of moratoir interest must be based on a Court Decision. The application of the imposition of moratoir interest in both cases shows equity in the application of the legal basis without neglecting justice and expediency, thus achieving a balance in achieving legal objectives according to Gustav Radbruch's theory. It can be concluded that the imposition of unspecified moratoir interest can be applied as a legal consequence in default as long as it is decided by a judge in court